Hypoxia and TLR9 activation drive CXCL4 production in systemic sclerosis plasmacytoid dendritic cells via mtROS and HIF-2α. (24th September 2021) - Ottria, Andrea; Zimmermann, Maili; Paardekooper, Laurent M; Carvalheiro, Tiago; Vazirpanah, Nadia; Silva-Cardoso, Sandra; Affandi, Alsya J; Chouri, Eleni; v.d Kroef, Maarten; Tieland, Ralph G; Bekker, Cornelis P J; Wichers, Catharina G K; et al.
Abstract: Objective: SSc is a complex disease characterized by vascular abnormalities and inflammation culminating in hypoxia and excessive fibrosis. Previously, we identified chemokine (C-X-C motif) ligand 4 (CXCL4) as a novel predictive biomarker in SSc. Although CXCL4 is well-studied, the mechanisms driving its production are unclear. The aim of this study was to elucidate the mechanisms leading to CXCL4 production. Methods: Plasmacytoid dendritic cells (pDCs) from 97 healthy controls and 70 SSc patients were cultured in the presence of hypoxia or atmospheric oxygen level and/or stimulated with several toll-like receptor (TLR) agonists. Further, pro-inflammatory cytokine production, CXCL4, hypoxia-inducible factor (HIF) -1α and HIF-2α gene and protein expression were assessed using ELISA, Luminex, qPCR, FACS and western blot assays. Results: CXCL4 release was potentiated only when pDCs were simultaneously exposed to hypoxia and TLR9 agonist ( P < 0.0001). Here, we demonstrated that CXCL4 production is dependent on the overproduction of mitochondrial reactive oxygen species (mtROS) ( P = 0.0079) leading to stabilization of HIF-2α ( P = 0.029). In addition, we show that hypoxia is fundamental for CXCL4 production by umbilical cord CD34 derived pDCs. Conclusion: TLR-mediated activation of immune cells in the presence of hypoxia underpins the pathogenic production of CXCL4 in SSc. Blocking either mtROS or HIF-2α pathways may therapeutically attenuate the contribution of CXCL4 to SSc and other inflammatory diseases driven by CXCL4.